2002
DOI: 10.1007/pl00012441
|View full text |Cite
|
Sign up to set email alerts
|

Skew loops and quadric surfaces

Abstract: Abstract.A skew loop is a closed curve without parallel tangent lines. We prove: The only complete surfaces in R 3 with a point of positive curvature and no skew loops are the quadrics. In particular: Ellipsoids are the only closed surfaces without skew loops. Our efforts also yield results about skew loops on cylinders and positively curved surfaces. Mathematics Subject Classification (2000). Primary 53A04, 53A05; Secondary 53C45, 52A15.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 22 publications
0
30
0
Order By: Relevance
“…Totally skew submanifolds (TS-embeddings) are generalizations of skew loops and skew branes [13,15,16,33] which are submanifolds in an affine space without parallel tangent spaces (S-embeddings). Skew loops were first studied by B. Segre [29] and have connections to quadric surfaces (skew branes were studied by Lai [25]; see also [34]).…”
Section: Theorem 14 If There Exists a Totally Skew Diskmentioning
confidence: 99%
See 1 more Smart Citation
“…Totally skew submanifolds (TS-embeddings) are generalizations of skew loops and skew branes [13,15,16,33] which are submanifolds in an affine space without parallel tangent spaces (S-embeddings). Skew loops were first studied by B. Segre [29] and have connections to quadric surfaces (skew branes were studied by Lai [25]; see also [34]).…”
Section: Theorem 14 If There Exists a Totally Skew Diskmentioning
confidence: 99%
“…Skew loops were first studied by B. Segre [29] and have connections to quadric surfaces (skew branes were studied by Lai [25]; see also [34]). In particular, the first author and Solomon [15] showed that the absence of skew loops characterizes quadric surfaces of positive curvature (including ellipsoids), while the second author [33] ruled out the existence of skew branes on quadric hypersurfaces in any dimension; see also [36] and [30]. Note, however, that skew loops are only affinely invariant, whereas quadric surfaces are invariant under the more general class of projective transformations.…”
Section: Theorem 14 If There Exists a Totally Skew Diskmentioning
confidence: 99%
“…Then g − c is a derivative, g(x) − c = −f ′ (x), and df + α = cdx. It follows that, in dimension one, Conjecture 3.1 holds as well: this the Cylinder Lemma of [6].…”
Section: Lemma 32mentioning
confidence: 82%
“…The generalization described in Remark 2.5 will remove the need to assume rotational symmetry. Still, the main theorem here yields a first negatively curved counterpart to the characterization of positively curved quadrics in [3].…”
Section: Remark 24 Though Stated In Rmentioning
confidence: 86%